Factors Affecting Initiation and Duration of Breastfeeding Among Off-Reserve Indigenous Children in Canada - Romano, Isabella; Cooke, Martin; Wilk, Piotr (International Indigenous Policy Journal, 2019)
Indigenous children in Canada are less likely to be breastfed compared to non-Indigenous children; however, little information about rates and correlates of breastfeeding exist. We used a nationally representative survey to examine breastfeeding initiation (n = 9,330) and duration (n = 6,760) among First Nations, Métis, and Inuit children. In our sample, 72.5% of children had been breastfed, and 57.9% of these individuals were breastfed until six months. Factors associated with increased breastfeeding included mothers' educational attainment, children's weight at birth, mothers' residential school attendance, and region of residence. Having Indian Status and lower household income were associated with lower breastfeeding initiation and duration. Our findings suggest that targeted efforts to encourage and support breastfeeding among Indigenous women are needed. Additional research using contemporary data are required in Canada.